(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2019)
Considering the importance of the Supreme Courts in the western societies, it will be analized the proceedings for the nomination of the Supreme Court ministers in the USA, in order to provide – for Brazilian jurists – a comparative and reflexive tool about the nomination process regarding the STF ministers in Brazil.